Decolonization of education in Latin America. A systematic review of current research trends - LINDQUIST SÁNCHEZ, Ricardo; GARCÍA GALVÁN, Rodolfo (Utopía y Praxis Latinoamericana, 2023)
The aim of this study is to characterize the research trends on educational decolonization in Latin America, during the period 2010-2020. Regarding the methodology, it was based on a systematic review of the literature in different academic bases and search engines. In total, 176 articles published in the last decade were analyzed. The results show that the most consolidated research trends are related to the teaching-decolonization binomials, indigenous peoples and interculturality, as well as to the epistemological discussion. On the other hand, art decolonization, curricular decolonization, teacher training, feminism, and the link between decolonization and disability represent emerging research agendas.